2023
DOI: 10.1101/2023.07.28.550894
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Neuron-specific IIS/FOXO Transcriptome in Aged Animals Reveals Regulatory Mechanisms of Cognitive Aging

Yifei Weng,
Shiyi Zhou,
Katherine Morillo
et al.

Abstract: Cognitive decline is a significant public health concern in our aging society. In this study, we used the model organism C. elegans to investigate the impact of the IIS/FOXO pathway on age-related cognitive decline. The daf-2 Insulin/IGF-1 receptor mutant exhibits a significant extension of learning and memory span with age compared to wild-type worms, an effect that is dependent on the DAF-16 transcription factor. To determine the mechanisms by which aging daf-2 mutants can maintain learning and memory with a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 99 publications
0
10
0
Order By: Relevance
“…We previously found that the insulin/IGF receptor mutant, daf-2, has extended short-term associative memory 1 , and its long-term memory is extended as well, through increased CREB expression 1,2 . daf-2 mutants also better maintain motor functions and axon regeneration ability with age [13][14][15] , and maintain their memory ability with age for twice as long as wild-type worms 16 . We are interested in how the daf-2 mutation changes the AWC transcriptome, as well as the transcriptomes of other neurons, to change learning ability and allow extended memory function.…”
Section: Introductionmentioning
confidence: 94%
See 4 more Smart Citations
“…We previously found that the insulin/IGF receptor mutant, daf-2, has extended short-term associative memory 1 , and its long-term memory is extended as well, through increased CREB expression 1,2 . daf-2 mutants also better maintain motor functions and axon regeneration ability with age [13][14][15] , and maintain their memory ability with age for twice as long as wild-type worms 16 . We are interested in how the daf-2 mutation changes the AWC transcriptome, as well as the transcriptomes of other neurons, to change learning ability and allow extended memory function.…”
Section: Introductionmentioning
confidence: 94%
“…In addition to their greatly extended lifespan, daf-2 mutants have improved and extended cognitive and neuronal behaviors 1,6,15,36 , some of which may depend on gene expression changes in individual neurons. We previously used pan-neuronal transcriptional profiling to identify genes whose expression is high in young wild-type neurons and declines with age 16 . These genes are enriched in neuronal and synaptic function 16,54 , and their downregulation with age correlates with behavioral deficits that rise with age.…”
Section: Genes That Normally Decline With Age Are Upregulated In Daf-...mentioning
confidence: 99%
See 3 more Smart Citations